2019
DOI: 10.1111/jam.14391
|View full text |Cite
|
Sign up to set email alerts
|

Antichagasic effect of violacein from Chromobacterium violaceum

Abstract: Aims: Violacein (VIO), a bacterial pigment produced by Chromobacterium violaceum, was examined to evaluate the antichagasic activity and its action mechanism against Trypanosoma cruzi Y strain. Methods and Results: Violacein was tested against the epimastigote, trypomastigote and amastigote forms of T. cruzi Y strain (benznidazoleresistant strain). VIO inhibited all T. cruzi developmental forms, including amastigotes, which is implicated in the burden of infection in the chronic phase of Chagas disease (CD). V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Currently, in our lab, calcium oxalate and uric acid stones dissolving pigments from marine bacteria are being isolated. Prodigiosin from S. marcescens [254] and violacein from C. violaceum [255] promise to treat the chagas disease. Violacein pigment is employed in cotton fabrics dyeing [256], and lead detecting whole-cell lead biosensor [257].…”
Section: Biomedical and Industrial Applicationsmentioning
confidence: 99%
“…Currently, in our lab, calcium oxalate and uric acid stones dissolving pigments from marine bacteria are being isolated. Prodigiosin from S. marcescens [254] and violacein from C. violaceum [255] promise to treat the chagas disease. Violacein pigment is employed in cotton fabrics dyeing [256], and lead detecting whole-cell lead biosensor [257].…”
Section: Biomedical and Industrial Applicationsmentioning
confidence: 99%
“…Similar results were previously reported for violacein extracts used against P. falciparum and P. chabaudi (Lopes et al 2009). In addition, Canuto et al (2019) reported ROS induction and changes in mitochondrial transmembrane using as potential action mechanisms.…”
Section: Violacein Effects On Parasites and On Their Vectorsmentioning
confidence: 99%
“…Violacein, a natural colorant produced by some Gramnegative bacteria, showed a predominantly apoptotic effect in developmental forms of T. cruzi (Y strain) and selectivity index of 9 (Canuto et al, 2019). However, the poor aqueous solubility of violacein is a serious obstacle for development pharmaceutical formulations.…”
Section: Lipid Nanosystems Encapsulating Non-approved Drugsmentioning
confidence: 99%